Analisis Visual Dalam Pemasaran Iklan Sprite “YANG-HAUS DIKEMACETAN" Tahun 2025 Menggunakan Metode Semantik - a'la illiyyin ahmad ahmad ayyin Ayyin; Eko Darmawanto (Citradirga : Jurnal Desain Komunikasi Visual dan Intermedia, 2025)
This study analyzes the visual messages in the 2025 "Yang-Haus" version of Sprite advertisements aired on YouTube. The research is driven by the significance of visual communication strategies in capturing consumer attention through advertising media. The objective is to identify the meaning of visual messages in each scene and how visual communication design elements are utilized to convey these messages. This study employs a qualitative method with a visual communication design approach, utilizing data collection techniques such as literature studies and visual analysis of each advertisement scene. The results indicate that the advertisement uses visual elements—such as a dominant green color, bold typography, water effects, and dramatic cinematography—to represent freshness, energy, and thirst-quenching qualities. Furthermore, symbols like lemons, soda bubbles, and character expressions strengthen the emotional message delivered to the audience. The study concludes that the "Yang-Haus" version of the Sprite advertisement does not merely provide product information but also builds a powerful visual experience to influence consumer perception and purchase intent.